Tractor display - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows two men and three tractors. One sign reads, "Dean Tractor and Implement Co., Sales - Service, 269 W. Santa Clara St., San Jose." Three signs read, "Cletrac Tank Type Tractor for Farm and Industrial Uses, Cleveland Tractor Co., Cleveland, Ohio, USA." Material from a large tent appears above and behind this scene.